2017
DOI: 10.1093/ajcp/aqx097
|View full text |Cite
|
Sign up to set email alerts
|

CD30 Expression in Monomorphic Posttransplant Lymphoproliferative Disorder, Diffuse Large B-Cell Lymphoma Correlates With Greater Regulatory T-Cell Infiltration

Abstract: These findings suggest a pathophysiologic link between CD30 activity and Tregs and may indicate differential expression of CD30 in B-cell lymphomas arising in the setting of immune dysregulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
6
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 26 publications
5
6
4
Order By: Relevance
“…In this nation-wide case series of 50 PTLDs after solid organ transplantation, 70% of the PTLDs expressed CD30 in the tumor cells and were thus potentially treatable with brentuximab vedotin. Previous case series have reported that 79-87% of the PTLDs were CD30þ [16][17][18]. In line with previous studies, we found that all Hodgkin lymphomas and polymorphic PTLDs and a vast majority of non-GC-type of DLBCLs and T-cell PTLDs were CD30þ, whereas GC-type of DLBCLs and Burkitt lymphomas were all CD30- [16,17,[23][24][25].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In this nation-wide case series of 50 PTLDs after solid organ transplantation, 70% of the PTLDs expressed CD30 in the tumor cells and were thus potentially treatable with brentuximab vedotin. Previous case series have reported that 79-87% of the PTLDs were CD30þ [16][17][18]. In line with previous studies, we found that all Hodgkin lymphomas and polymorphic PTLDs and a vast majority of non-GC-type of DLBCLs and T-cell PTLDs were CD30þ, whereas GC-type of DLBCLs and Burkitt lymphomas were all CD30- [16,17,[23][24][25].…”
Section: Discussionsupporting
confidence: 91%
“…In line with previous studies, we found that all Hodgkin lymphomas and polymorphic PTLDs and a vast majority of non-GC-type of DLBCLs and T-cell PTLDs were CD30þ, whereas GC-type of DLBCLs and Burkitt lymphomas were all CD30- [16,17,[23][24][25]. Furthermore, CD30þ PTLDs have been associated with EBVpositivity by EBER ISH [16][17][18]. We saw a trend that CD30þ PTLDs were more frequently EBVþ either when analyzed by EBER ISH or by LMP-1 IHC but numbers were too small to prove an association.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations